Hypericum L. ecobiology, medicinal properties (The Peerian Journal, 2022)
Hypericum L. is a family of grasses or shrubs in the steppe family. There are about 200 species, most of which grow in the Mediterranean. There are 3 types in Uzbekistan. Contains nutrients, essential oils and vitamin C. It is used in folk medicine (in diseases of the gastrointestinal tract and bloody diarrhea)